Polishing liquid composition

JP2023173782A5Active Publication Date: 2025-03-26KAO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022086266
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-05-26
Publication Date
2025-03-26
Estimated Expiration
2042-05-26

AI Technical Summary

Technical Problem

The increasing recording density in magnetic disk drives leads to drive failures due to silica particles remaining on the substrate surface after polishing, which are not effectively addressed by existing polishing technologies, and reducing particle size to minimize residue decreases the polishing rate.

Method used

A polishing liquid composition comprising silica particles with an ignition loss of 4% or less and a nitrogen-containing organic amine compound is used to maintain polishing rate while reducing silica residue.

Benefits of technology

The composition effectively reduces silica residue on the substrate surface while maintaining polishing efficiency, improving substrate quality and productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000019_0000
    Figure 00000019_0000
Patent Text Reader

Abstract

To provide a polishing liquid composition that can reduce residual silica on the substrate surface after polishing, while maintaining the polishing speed.SOLUTION: According to one embodiment, a polishing liquid composition contains silica particles, a nitrogen-containing compound, and an aqueous medium. The silica particles have an ignition loss of 4% or less on a dry weight basis. The nitrogen-containing compound is an organic amine compound having four or less nitrogen atoms in each molecule.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present disclosure relates to a polishing composition, a method for producing a magnetic disk substrate, and a method for polishing a substrate. [Background technology]

[0002] In recent years, magnetic disk drives have become smaller and their capacities have increased, resulting in a demand for higher recording densities. To achieve higher recording densities, it is necessary to reduce the unit recording area and improve the detection sensitivity of weakened magnetic signals. To achieve this, technological development is underway to further lower the flying height of magnetic heads. To ensure a lower flying height for magnetic heads and a larger recording area, magnetic disk substrates are subject to stringent requirements for improved smoothness and flatness (reduced surface roughness, waviness, and edge sagging) and reduced surface defects (reduced residual abrasive grains, scratches, protrusions, pits, etc.).

[0003] In response to such demands, in order to achieve both improved surface quality (smoother and fewer scratches) and improved productivity, a multi-stage polishing method having two or more polishing steps is often adopted in the manufacturing method of a magnetic disk substrate. Generally, to satisfy the demand for smoothness, an abrasive containing colloidal silica particles is used, and in order to improve productivity, a polishing composition containing alumina particles as abrasive grains is used. However, when alumina particles are used as abrasive grains, the penetration of the alumina particles into the substrate can cause defects in the magnetic disk substrate or in a magnetic disk having a magnetic layer applied to the magnetic disk substrate.

[0004] Therefore, for example, Patent Documents 1 and 2 propose polishing compositions that do not contain alumina particles but contain silica particles as abrasive grains. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 2017-19978 [Patent Document 2] Patent Publication No. 2021-175774 Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, as the recording density of magnetic disk drives has increased, the read head has come to be positioned within a few nanometers of the substrate, which is rotating at high speed. Drive failures have occurred due to the low position of the read head. As a result of the inventors' investigations, it was found that silica particles remaining on the substrate surface after polishing (hereinafter also referred to as "residual silica") are one of the causes of drive failures. It was also found that the amount of residual silica correlates with the size of the silica particles, which are the abrasive grains. The residual silica can be reduced by reducing the particle size of the silica abrasive, but reducing the particle size of the abrasive also reduces the polishing rate.

[0007] Therefore, in one aspect, the present disclosure provides a polishing liquid composition that can improve the removal rate without significantly increasing the amount of residual silica. In another aspect, the present disclosure provides a polishing liquid composition that can reduce the amount of residual silica on the substrate surface after polishing while maintaining the removal rate. [Means for solving the problem]

[0008] In one aspect, the present disclosure relates to a polishing liquid composition comprising silica particles, a nitrogen-containing compound, and an aqueous medium, wherein the silica particles have an ignition loss of 4% or less on a dry weight basis, and the nitrogen-containing compound is an organic amine compound having four or less nitrogen atoms in the molecule.

[0009] In one aspect, the present disclosure relates to a method for producing a magnetic disk substrate, which includes a polishing step of polishing a substrate to be polished with the polishing liquid composition of the present disclosure.

[0010] In one aspect, the present disclosure relates to a method for polishing a substrate, which comprises polishing the substrate to be polished with the polishing liquid composition of the present disclosure, wherein the substrate to be polished is a substrate used in the production of magnetic disk substrates.

[0011] In one aspect, the present disclosure relates to a method for reducing residual silica on a substrate after polishing, the method comprising polishing a substrate to be polished with the polishing liquid composition of the present disclosure.

[0012] In one aspect, the present disclosure relates to a method for manufacturing a magnetic disk substrate, comprising the steps of selecting silica particles as abrasive grains having an ignition loss of 4% or less on a dry weight basis, and polishing a substrate to be polished using a polishing composition containing the silica particles, a nitrogen-containing compound, and an aqueous medium, wherein the nitrogen-containing compound is an organic amine compound having four or less nitrogen atoms in its molecule. [Effects of the Invention]

[0013] According to one aspect of the present disclosure, it is possible to provide a polishing liquid composition that can improve the removal rate without significantly increasing the amount of residual silica. In another aspect, the present disclosure is possible to provide a polishing liquid composition that can reduce the amount of residual silica on the substrate surface after polishing while maintaining the removal rate. [Brief explanation of the drawings]

[0014] [Figure 1] FIG. 1 is an example of a transmission electron microscope (hereinafter also referred to as "TEM") photograph of the confetti-shaped colloidal silica abrasive grains. [Figure 2] Figure 2 shows an example of a TEM observation photograph of irregular-shaped colloidal silica abrasive grains. DETAILED DESCRIPTION OF THE INVENTION

[0015] Measuring silica particles (silica residues) remaining on the substrate surface after polishing is time-consuming and has rarely been recognized as an item for evaluating the quality of the substrate surface after polishing, and has not been recognized as a cause of drive failure. Note that the "silica residues" that were considered a problem in conventional technology are physical defects such as particles embedded in scratches or punctures, and are relatively easily detectable using model tests with simple cleaning or an electron microscope, and therefore have different issues and effects from the "silica residues" in this disclosure. In Patent Document 1, heat-treated silica, which generally has a high surface hardness, is used, which has the problem of a tendency for recess defects and protrusions to occur on the substrate surface. In addition, Patent Document 2 achieves both a high removal rate and excellent substrate surface quality, but further improvement in removal rate is desired in terms of improving substrate productivity. However, Patent Documents 1 and 2 do not address the problem of reducing residual silica. In one aspect, the present disclosure is based on the discovery that the amount of residual silica correlates with the ignition loss of silica abrasive grains, and further based on the discovery that the removal rate can be improved without significantly increasing the amount of residual silica by using silica abrasive grains having an ignition loss of a predetermined value or less in combination with a specific nitrogen-containing compound.

[0016] That is, in one aspect, the present disclosure relates to a polishing liquid composition (hereinafter also referred to as the "polishing liquid composition of the present disclosure") that contains silica particles, a nitrogen-containing compound, and an aqueous medium, wherein the silica particles have an ignition loss of 4% or less on a dry weight basis, and the nitrogen-containing compound is an organic amine compound having four or less nitrogen atoms in the molecule.

[0017] The mechanism by which the effects of the present disclosure are manifested is not clear, but is speculated as follows. As a result of our investigations, we believe that residual silica, which leads to drive failure, is related to hydrogen bonding between the silanol groups of silica particles and the substrate surface. However, the amount of residual silica shows only a weak correlation with the "silanol group density" of silica abrasive grains compared to the ignition loss of silica abrasive grains. It is believed that an additional mechanism is involved in the correlation between the amount of residual silica and the ignition loss. If the ignition loss is set to a certain value or less to reduce the residual silica, and then the average particle size of the silica abrasive grains is simply increased in order to further improve the polishing rate, the residual silica will also worsen. Therefore, the present inventors have focused on the fact that by using an organic amine compound having a nitrogen atom, the organic amine compound acts on both the substrate and the silica abrasive grains, thereby improving the polishing rate. Furthermore, they have found that by setting the number of nitrogen atoms in the molecule of the organic amine compound to 4 or less, the silica abrasive grains are not attracted too much to the substrate, and easy cleaning is maintained, so that the residual silica will not be significantly worsened. However, the present disclosure need not be construed as being limited to these mechanisms.

[0018] [Silica particles A (component A)] The polishing liquid composition of the present disclosure contains silica particles A (hereinafter also referred to as "component A") as abrasive grains. In one or more embodiments, from the viewpoint of improving the polishing rate without significantly increasing the amount of residual silica, the silica particles A (component A) are preferably silica particles having an ignition loss of 4% or less on a dry weight basis, and a D90 of 140 nm or more and 600 nm or less, where D90 is the particle diameter at which a cumulative frequency from the small particle size side in a particle size distribution calculated by weight obtained by centrifugal sedimentation is 90%. Component A is preferably used in the form of a slurry polishing liquid component. Component A may be used alone or in combination of two or more types.

[0019] The particle diameter D10 of component A measured by centrifugal sedimentation in terms of weight is preferably 50 nm or more, more preferably 52 nm or more, and even more preferably 53 nm or more, from the viewpoint of maintaining the polishing rate, and is preferably 120 nm or less, more preferably 100 nm or less, and even more preferably 60 nm or less, from the viewpoint of the substrate surface quality. More specifically, the particle diameter D50 of component A measured by centrifugal sedimentation is 50 nm or more and 120 nm or less, more preferably 52 nm or more and 100 nm or less, and even more preferably 53 nm or more and 60 nm or less.

[0020] The particle diameter D50 of component A measured by centrifugal sedimentation in terms of weight is preferably 80 nm or more, more preferably 85 nm or more, and even more preferably 90 nm or more, from the viewpoint of maintaining the polishing rate, and is preferably 340 nm or less, more preferably 200 nm or less, and even more preferably 110 nm or less, from the viewpoint of the substrate surface quality. More specifically, the particle diameter D50 of component A measured by centrifugal sedimentation is 80 nm or more and 340 nm or less, more preferably 85 nm or more and 200 nm or less, and even more preferably 90 nm or more and 110 nm or less.

[0021] The particle diameter D90 of component A measured by centrifugal sedimentation in terms of weight is preferably 140 nm or more, more preferably 150 nm or more, even more preferably 160 nm or more, and even more preferably 170 nm or more, from the viewpoint of maintaining the polishing rate, and from the viewpoint of reducing residual silica, it is preferably 600 nm or less, more preferably 500 nm or less, even more preferably 400 nm or less, and even more preferably 250 nm or less. More specifically, the particle diameter D90 of component A measured by centrifugal sedimentation is preferably 140 nm or more and 600 nm or less, more preferably 150 nm or more and 500 nm or less, even more preferably 160 nm or more and 400 nm or less, and even more preferably 170 nm or more and 250 nm or less.

[0022] In the present disclosure, D10, D50, and D90 refer to the particle sizes at which the cumulative frequency from the small diameter side in the particle size distribution obtained by centrifugal sedimentation in terms of weight is 10%, 50%, and 90%, respectively. In the present disclosure, centrifugal sedimentation, in one or more embodiments, is a method of classifying and detecting particles by size based on differences in sedimentation velocity (disk centrifugal sedimentation light transmission method). Particle size distribution by centrifugal sedimentation can be measured, for example, using a disc centrifugal particle size distribution analyzer (CPS Disc Centrifuge). In the following description, particle size distribution by centrifugal sedimentation is sometimes referred to as "particle size distribution by CPS measurement." Specifically, it can be calculated using the measurement method described in the Examples.

[0023] Examples of methods for adjusting the particle size distribution of component A by centrifugal sedimentation include methods for adjusting the particle growth time, particle temperature, particle concentration, etc. during the growth process of silica particles. Other embodiments of methods for adjusting the particle size distribution of component A by centrifugal sedimentation include methods for imparting a desired particle size distribution by adding new nucleus particles during the particle growth process in the production stage, and methods for imparting a desired particle size distribution by mixing two or more types of silica particles having different particle size distributions.

[0024] From the viewpoint of maintaining the polishing rate, the average secondary particle diameter of component A is preferably 100 nm or more, more preferably 110 nm or more, and even more preferably 130 nm or more. From the viewpoint of substrate surface quality, it is preferably 340 nm or less, more preferably 200 nm or less, and even more preferably 180 nm or less. More specifically, the average secondary particle diameter of component A is preferably 100 nm or more and 340 nm or less, more preferably 110 nm or more and 200 nm or less, and even more preferably 130 nm or more and 180 nm or less. In this disclosure, the average secondary particle diameter of component A refers to the average particle diameter based on the scattering intensity distribution measured by dynamic light scattering. In this disclosure, the "scattering intensity distribution" refers to the volume-equivalent particle size distribution of submicron particles determined by dynamic light scattering (DLS) or quasielastic light scattering (QLS). The average secondary particle diameter of component A in this disclosure can be specifically obtained by the method described in the Examples.

[0025] The ignition loss of component A on a dry weight basis is 4% or less, preferably 3.6% or less, more preferably 3.5% or less, and even more preferably 3.4% or less, from the viewpoint of reducing residual silica, and from the viewpoint of storage stability, is preferably 0% or more, more preferably 1% or more, and even more preferably 2% or more. More specifically, the ignition loss of component A on a dry weight basis is preferably 0% or more and 3.6% or less, more preferably 1% or more and 3.5% or less, and even more preferably 2% or more and 3.4% or less. In one or more embodiments of the present disclosure, the loss on ignition (WL) on a dry weight basis is a value calculated from the following formula: A sample is prepared by mixing silica particles with water to form a silica slurry, drying it at a constant temperature between 105°C and 180°C, allowing it to stand and return to room temperature, and then drying it at a constant temperature between 105°C and 180°C. The loss on drying (LOD) (wt%) is measured, and the loss on ignition (LOI) (wt%) is measured after the sample is heat-treated at 800°C or higher. Specifically, the calculation can be performed using the method described in the Examples. It can be evaluated that the smaller the loss on ignition (WL), the fewer the total number of silanol groups contained in 1 g of abrasive grain. Loss on ignition (WL) on a dry weight basis = 100 × {1-(100-LOI) / (100-LOD)}

[0026] Examples of methods for adjusting the ignition loss of component A include adjusting the dropping rate, reaction temperature, and concentration of the silicic acid solution during the growth of silica particles. Other embodiments of the method for adjusting the ignition loss of component A include adjusting the desired ignition loss by subjecting existing silica particles to heat treatment, metal modification of surface silanol groups, organic acid modification, or silane coupling treatment, and mixing two or more types of silica particles having different ignition losses to achieve the desired ignition loss.

[0027] An index that shows a stronger correlation with residual silica than "loss on ignition" is "the value represented by the following formula (I) when WL is the loss on ignition based on the dry weight of component A." From the viewpoint of reducing residual silica, the value represented by the following formula (I) when WL is the loss on ignition based on the dry weight of component A is preferably 150 or less, more preferably 100 or less, even more preferably 90 or less, and even more preferably 85 or less. From the viewpoint of maintaining the polishing rate and storage stability, the value is preferably 10 or more, more preferably 20 or more, even more preferably 40 or more, and even more preferably 60 or more. More specifically, the value represented by the following formula (I) is preferably 10 or more and 150 or less, more preferably 20 or more and 100 or less, even more preferably 40 or more and 90 or less, and even more preferably 60 or more and 85 or less. {(WL) 3 ×D90} / 100 (I) By setting the value represented by the above formula (I) to a predetermined value or less, it is possible to achieve both a high effect of reducing residual silica and a good polishing rate.

[0028] Examples of Component A include colloidal silica, wet-process silica (precipitated silica), fumed silica, pulverized silica, and surface-modified silica thereof. From the viewpoints of maintaining the polishing rate and easy availability, Component A is preferably at least one selected from colloidal silica and wet-process silica, and from the viewpoint of substrate surface quality, colloidal silica, which is less likely to give a sharp surface shape or localized high surface hardness sites, is more preferred. The colloidal silica may be obtained, for example, by a method of particle growth using an aqueous alkali silicate solution as a raw material (hereinafter also referred to as the "water glass method"), or by a method of condensation of a hydrolyzate of an alkoxysilane (hereinafter also referred to as the "sol-gel method"), and from the viewpoints of ease of production and economic efficiency, the colloidal silica obtained by the water glass method is preferred. Silica particles obtained by the water glass method and the sol-gel method can be produced by conventionally known methods. The precipitated silica is silica particles obtained by a precipitation method. Examples of methods for producing precipitated silica particles include known methods such as those described in Tosoh Research and Technical Report, Vol. 45 (2001), pp. 65-69. A specific example of a method for producing precipitated silica particles is a precipitation method in which silica particles are precipitated by a neutralization reaction between a silicate, such as sodium silicate, and a mineral acid, such as sulfuric acid. The neutralization reaction is preferably carried out under alkaline conditions at a relatively high temperature, which allows the growth of primary silica particles to proceed rapidly, resulting in the primary particles flocculating and settling. The precipitated silica particles are preferably obtained by further pulverizing the flocs.

[0029] The shape of Component A may be either non-spherical or spherical. In one or more embodiments, Component A may contain spherical silica particles and non-spherical silica particles. In the present disclosure, the average aspect ratio of the spherical silica particles is preferably 1.00 or more, more preferably 1.02 or more, from the viewpoint of maintaining the polishing rate, and is preferably 1.20 or less, more preferably 1.1 or less, and even more preferably 1.06 or less, from the viewpoint of the substrate surface quality. The average aspect ratio of the non-spherical silica particles is preferably 1.00 or more, more preferably 1.02 or more, from the viewpoint of maintaining the polishing rate, and is preferably 1.30 or less, more preferably 1.15 or less, and even more preferably 1.10 or less, from the viewpoint of the substrate surface quality. The average aspect ratio is the simple average of the major axis / minor axis ratios of the smallest inscribed squares determined for each particle using a known scanning electron microscope (SEM) and a known image analysis system.

[0030] When component A contains non-spherical silica particles, the shape of the non-spherical silica particles may be, from the viewpoint of maintaining the polishing rate and the surface quality of the substrate, a shape in which a plurality of precursor particles having a particle size smaller than the secondary particle size of the non-spherical silica particles are aggregated or fused together. Examples of the type of non-spherical silica particles include at least one type selected from confetti-shaped silica particles Aa, irregular shaped silica particles Ab, and irregular confetti-shaped silica particles Ac.

[0031] In the present disclosure, spinous silica particles Aa (hereinafter also referred to as "particles Aa") refer to silica particles having unique wart-like protrusions on the spherical particle surface. Particles Aa preferably have a shape formed by agglomeration or fusion of the largest precursor particle a1 and one or more precursor particles a2, each having a particle size 1 / 5 or less of that of the precursor particle a1. Particles Aa preferably have a state in which multiple smaller precursor particles a2 are partially embedded in one larger precursor particle a1. Particles Aa can be obtained, for example, by the method described in JP 2008-137822 A. The particle size of the precursor particle can be determined as the circle-equivalent diameter measured within a single precursor particle in an image observed by TEM or the like, i.e., the major axis of a circle having the same area as the projected area of ​​the precursor particle. The particle sizes of the precursor particles in irregularly shaped silica particles Ab and irregularly shaped spinous silica particles Ac can also be determined in a similar manner.

[0032] In the present disclosure, irregularly shaped silica particles Ab (hereinafter also referred to as "particles Ab") refer to silica particles having a shape formed by aggregation or fusion of two or more precursor particles, preferably two to ten precursor particles (see FIG. 1). The particles Ab preferably have a shape formed by aggregation or fusion of two or more precursor particles having a particle size within 1.5 times the particle size of the smallest precursor particle. The particles Ab can be obtained, for example, by the method described in JP 2015-86102 A.

[0033] In the present disclosure, irregularly shaped, confetti-shaped silica particles Ac (hereinafter also referred to as "particles Ac") have a shape in which the particles Ab are precursor particles c1, and the largest precursor particle c1 is aggregated or fused with one or more precursor particles c2 whose particle size is 1 / 5 or less of that of the precursor particle c1.

[0034] The content of component A in the polishing composition of the present disclosure is, in terms of SiO2, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, and even more preferably 2% by mass or more, from the viewpoint of maintaining the polishing rate and the substrate surface quality. From the viewpoint of economic efficiency, it is preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less, and even more preferably 15% by mass or less. More specifically, the content of component A is preferably 0.1% by mass or more and 30% by mass or less, more preferably 0.5% by mass or more and 25% by mass or less, even more preferably 1% by mass or more and 20% by mass or less, and even more preferably 2% by mass or more and 15% by mass or less. When component A consists of two or more types of silica particles, the content of component A refers to the total content thereof.

[0035] When Component A contained in the polishing liquid composition of the present disclosure contains spherical silica particles and non-spherical silica particles, from the viewpoints of maintaining the polishing rate and the substrate surface quality, the proportion of spherical silica particles in Component A is preferably 10% or more, more preferably 20% or more, even more preferably 30% or more, and preferably less than 100%, more preferably 80% or less, and even more preferably 70% or less. From the same viewpoint, the proportion of non-spherical silica particles in Component A is preferably 90% or less, more preferably 80% or less, even more preferably 70% or less, and preferably more than 0%, more preferably 20% or more, and even more preferably 30% or more.

[0036] [Nitrogen-containing compounds] The polishing liquid composition of the present disclosure contains a nitrogen-containing compound (hereinafter also referred to as "component D") from the viewpoint of improving the polishing rate without significantly increasing the amount of residual silica. In one or more embodiments, component D is an organic amine compound having four or less nitrogen atoms in the molecule. From the viewpoint of improving the polishing rate without significantly increasing the amount of residual silica, component D is preferably one or more compounds having any of primary to tertiary amino groups. In one or more embodiments, component D may have a hydroxy group from the viewpoint of workability taking into account odor and / or boiling point. Component D may be one type or a combination of two or more types.

[0037] The number of nitrogen atoms in the molecule of component D is preferably 1, 2 or 3, and more preferably 1 or 2, from the viewpoint of improving the polishing rate without significantly increasing the amount of residual silica.

[0038] From the viewpoint of improving the polishing rate without significantly increasing the amount of residual silica, in one or more embodiments, Component D is at least one compound selected from aliphatic amine compounds having four or less nitrogen atoms in the molecule and alicyclic amine compounds having four or less nitrogen atoms in the molecule. From the same viewpoint, examples of the aliphatic amine compound include at least one selected from monoethanolamine, ethylenediamine, N,N,N',N'-tetramethylethylenediamine, 1,2-diaminopropane, 1,3-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, 3-(diethylamino)propylamine, 3-(dibutylamino)propylamine, 3-(methylamino)propylamine, 3-(dimethylamino)propylamine, N-aminoethylethanolamine, N-(2-aminoethyl)diethanolamine, N-aminoethylisopropanolamine, N-aminoethyl-N-methylethanolamine, diethylenetriamine, and triethylenetetramine. Of these, at least one selected from monoethanolamine (MEA), N-aminoethylethanolamine (AEA), diethylenetriamine (DETA), and triethylenetetramine (TETA) is preferred. From the same viewpoint, examples of the alicyclic amine compound include at least one selected from piperazine, 2-methylpiperazine, 2,5-dimethylpiperazine, 1-amino-4-methylpiperazine, N-methylpiperazine, 1-(2-aminoethyl)piperazine, hydroxyethylpiperazine, and piperazine-1,4-bisethanol, and among these, hydroxyethylpiperazine (HEP) is preferred.

[0039] In one or more embodiments, the molecular weight of Component D is preferably 60 or more and 500 or less, more preferably 60 or more and 300 or less, even more preferably 60 or more and 150 or less, and still more preferably 60 or more and 135 or less, from the viewpoint of improving the polishing rate without significantly increasing the amount of residual silica.

[0040] From the viewpoint of improving the polishing rate without significantly increasing the amount of residual silica, the content of component D in the polishing liquid composition of the present disclosure is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.03% by mass or more, and from the same viewpoint, it is preferably 1% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.3% by mass or less. More specifically, the content of component D in the polishing liquid composition of the present disclosure is preferably 0.001% by mass or more and 1% by mass or less, more preferably 0.01% by mass or more and 0.5% by mass or less, and even more preferably 0.03% by mass or more and 0.3% by mass or less.

[0041] In one or more embodiments, the mass ratio D / A of the content of component D to the content of component A in the polishing liquid composition of the present disclosure is preferably 0.00018 or more, more preferably 0.0018 or more, and even more preferably 0.0054 or more, from the viewpoint of improving the polishing rate without significantly increasing the amount of residual silica, and from the same viewpoint, is preferably 0.18 or less, more preferably 0.09 or less, and even more preferably 0.054 or less. More specifically, the mass ratio D / A is preferably 0.00018 or more and 0.18 or less, more preferably 0.0018 or more and 0.09 or less, and even more preferably 0.0054 or more and 0.054 or less.

[0042] [Aqueous medium] Examples of the aqueous medium contained in the polishing liquid composition of the present disclosure include water such as distilled water, ion-exchanged water, pure water, and ultrapure water, or a mixed solvent of water and a solvent. Examples of the solvent include a solvent miscible with water (e.g., an alcohol such as ethanol). When the aqueous medium is a mixed solvent of water and a solvent, the proportion of water in the entire mixed medium is not particularly limited as long as the effects of the present disclosure are not impaired. From an economical standpoint, for example, the proportion of water in the entire mixed medium is preferably 95% by mass or more, more preferably 98% by mass or more, and even more preferably substantially 100% by mass. The content of the aqueous medium in the polishing liquid composition of the present disclosure can be the remainder excluding component A, component D, and the optional components described below (component B, component C, and other components) that are blended as needed.

[0043] [Acid (component B)] The polishing composition of the present disclosure may contain an acid (hereinafter also referred to as "Component B") from the viewpoint of further improving the removal rate and further reducing short-wavelength waviness. In the present disclosure, the use of an acid includes the use of an acid and / or a salt thereof. Component B may be one type or a combination of two or more types. Examples of Component B include inorganic acids such as nitric acid, sulfuric acid, sulfurous acid, persulfuric acid, hydrochloric acid, perchloric acid, phosphoric acid, phosphonic acid, phosphinic acid, pyrophosphoric acid, polyphosphoric acid, and amidosulfuric acid; and organic acids such as organic phosphoric acid and organic phosphonic acid. Among these, from the viewpoint of further improving the polishing rate and further reducing the short-wavelength waviness, Component B is preferably at least one selected from phosphoric acid, sulfuric acid, and 1-hydroxyethylidene-1,1-diphosphonic acid, more preferably at least one selected from sulfuric acid and phosphoric acid, and even more preferably phosphoric acid. Examples of salts of these acids include salts of the above acids with at least one selected from metals, ammonia, and alkylamines. Specific examples of the above metals include metals belonging to Groups 1 to 11 of the periodic table. Among these, from the viewpoint of further improving the polishing rate and further reducing the short-wavelength waviness, salts of the above acids with metals belonging to Group 1 or ammonia are preferred.

[0044] When the polishing composition of the present disclosure contains component B, the content of component B in the polishing composition of the present disclosure is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, from the viewpoint of further improving the removal rate and further reducing short-wavelength waviness. From the same viewpoint, it is preferably 5% by mass or less, more preferably 4% by mass or less, even more preferably 3% by mass or less, and even more preferably 2.5% by mass or less. More specifically, the content of component B is preferably 0.001% by mass or more and 5% by mass or less, more preferably 0.01% by mass or more and 4% by mass or less, even more preferably 0.05% by mass or more and 3% by mass or less, and even more preferably 0.1% by mass or more and 2.5% by mass or less. When component B is a combination of two or more types, the content of component B refers to the total content thereof.

[0045] [Oxidizing agent (component C)] The polishing composition of the present disclosure may contain an oxidizing agent (hereinafter also referred to as "component C") from the viewpoint of further improving the removal rate and further reducing short-wavelength waviness. Component C may be one type or a combination of two or more types. From the same viewpoint, examples of component C include peroxides, permanganic acid or its salts, chromic acid or its salts, peroxoacids or their salts, oxyacids or their salts, nitric acids, sulfuric acids, etc. Among these, component C is preferably at least one selected from hydrogen peroxide, iron(III) nitrate, peracetic acid, ammonium peroxodisulfate, iron(III) sulfate, and ammonium iron(III) sulfate, and hydrogen peroxide is more preferred from the viewpoints of improving the polishing rate, preventing metal ions from adhering to the surface of the substrate to be polished, and ease of availability.

[0046] When the polishing liquid composition of the present disclosure contains component C, the content of component C in the polishing liquid composition of the present disclosure is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, from the viewpoint of further improving the removal rate, and is preferably 4% by mass or less, more preferably 2% by mass or less, and even more preferably 1.5% by mass or less, from the viewpoint of further improving the removal rate and further reducing short-wavelength waviness. More specifically, the content of component C is preferably 0.01% by mass or more and 4% by mass or less, more preferably 0.05% by mass or more and 2% by mass or less, and even more preferably 0.1% by mass or more and 1.5% by mass or less. When component C is a combination of two or more types, the content of component C refers to the total content thereof.

[0047] [Other ingredients] The polishing composition of the present disclosure may contain other components as needed. Examples of other components include corrosion inhibitors, thickeners, dispersants, rust inhibitors, basic substances, surfactants, and water-soluble polymers. The other components are preferably contained in the polishing composition to a degree that does not impair the effects of the present disclosure. When other components are contained, the content of the other components in the polishing composition of the present disclosure is preferably 0% by mass or more, more preferably greater than 0% by mass, even more preferably 0.1% by mass or more, and preferably 10% by mass or less, and more preferably 5% by mass or less. More specifically, the content is preferably 0% by mass or more and 10% by mass or less, more preferably greater than 0% by mass or more and 10% by mass or less, even more preferably 0.1% by mass or more and 10% by mass or less, even more preferably 0.1% by mass or more and 5% by mass or less.

[0048] [Alumina abrasive grains] From the viewpoint of reducing protrusion defects, the polishing liquid composition of the present disclosure preferably contains substantially no alumina abrasive grains. In one or more embodiments, the term "substantially does not contain alumina abrasive grains" in the present disclosure may mean that the composition does not contain alumina particles, does not contain alumina particles in an amount that functions as abrasive grains, or does not contain alumina particles in an amount that would affect the polishing results. Specifically, from the viewpoint of reducing protrusion defects, the content of alumina abrasive grains in the polishing liquid composition of the present disclosure is preferably 5% by mass or less, more preferably 2% by mass or less, even more preferably 1% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.05% by mass or less, even more preferably 0.02% by mass or less, and even more preferably substantially 0% by mass. Furthermore, in one or more embodiments, the content of alumina particles in the polishing liquid composition of the present disclosure is preferably 2% by mass or less, more preferably 1% by mass or less, even more preferably 0.5% by mass or less, and even more preferably substantially 0% by mass, relative to the total amount of abrasive grains in the polishing liquid composition.

[0049] [pH] From the viewpoint of substrate surface quality, the pH of the polishing composition of the present disclosure is preferably 0.5 or higher, more preferably 0.7 or higher, even more preferably 0.9 or higher, and even more preferably 1 or higher. From the viewpoint of maintaining the polishing rate, the pH is preferably 9 or lower, more preferably 6 or lower, even more preferably 4 or lower, even more preferably 3 or lower, even more preferably 2.5 or lower, and even more preferably 2 or lower. More specifically, the pH of the polishing composition of the present disclosure is preferably 0.5 or higher and 9 or lower, more preferably 0.5 or higher and 6 or lower, even more preferably 0.7 or higher and 4 or lower, even more preferably 1 or higher and 3 or lower, even more preferably 1 or higher and 2.5 or lower, and even more preferably 1 or higher and 2 or lower. The pH can be adjusted using the aforementioned acid (component B) or a known pH adjuster. The above pH is the pH of the polishing composition at 25°C and can be measured using a pH meter, preferably the value measured 2 minutes after immersing the pH meter electrode in the polishing composition.

[0050] [Method of manufacturing the polishing composition] The polishing liquid composition of the present disclosure can be produced, for example, by blending component A, component D, an aqueous medium, and, if necessary, optional components (component B, component C, and other components) using a known method. Therefore, in one aspect, the present disclosure relates to a method for producing a polishing liquid composition, comprising blending at least component A, component D, and an aqueous medium. In the present disclosure, "blending" includes mixing component A, component D, an aqueous medium, and, if necessary, optional components (component B, component C, and other components) simultaneously or in any order. The blending can be carried out using a mixer such as a homomixer, a homogenizer, an ultrasonic disperser, or a wet ball mill. The preferred blend amounts of each component in the methods for producing silica slurries and polishing liquid compositions can be the same as the preferred contents of each component in the polishing liquid compositions of the present disclosure described above.

[0051] In the present disclosure, the "content of each component in the polishing composition" refers to the content of each component at the time of use, that is, at the time when the polishing composition is first used for polishing. The polishing composition of the present disclosure may be stored and supplied in a concentrated state as long as its storage stability is not impaired. This is preferable because it can further reduce production and transportation costs. The concentrated polishing composition of the present disclosure may be appropriately diluted with the above-mentioned water as needed before use.

[0052] [Polishing liquid kit] In one aspect, the present disclosure relates to a polishing liquid kit for producing the polishing liquid composition of the present disclosure, the polishing liquid kit comprising a container-packed silica dispersion containing component A and an aqueous medium (hereinafter also referred to as the "polishing liquid kit of the present disclosure"). The polishing liquid kit according to the present disclosure may further comprise an aqueous additive solution containing component D and, if necessary, component B and component C, which are stored in a container separate from the container-packed silica dispersion. According to one or more embodiments of the present disclosure, a polishing liquid composition capable of improving the polishing rate without significantly increasing the amount of residual silica can be obtained. Furthermore, in one or more other embodiments, a polishing liquid composition capable of reducing the amount of residual silica on the substrate surface after polishing while maintaining the polishing rate can be obtained. In one or more embodiments, the polishing liquid kit of the present disclosure may be, for example, a polishing liquid kit (two-component polishing liquid composition) that contains a silica dispersion (slurry) containing component A and an aqueous medium, and component D, and an additive aqueous solution containing components B and C, if necessary, in a mutually unmixed state, which are mixed at the time of use and diluted with an aqueous medium as needed. The aqueous medium contained in the silica dispersion may be the entire amount of the aqueous medium used to prepare the polishing liquid composition, or may be a portion thereof. The silica dispersion and the additive aqueous solution may each contain the other components described above as needed.

[0053] [Substrate to be polished] In one or more embodiments, the substrate to be polished is a substrate used in the manufacture of a magnetic disk substrate, such as a Ni-P-plated aluminum alloy substrate. In the present disclosure, the term "Ni-P-plated aluminum alloy substrate" refers to an aluminum alloy substrate whose surface is ground and then electroless Ni-P-plated. A magnetic disk substrate can be manufactured by polishing the surface of the substrate to be polished using the polishing composition of the present disclosure, followed by a step of forming a magnetic layer on the substrate surface by sputtering or the like. The shape of the substrate to be polished may be, for example, a disk-shaped, plate-shaped, slab-shaped, or prism-shaped shape with a flat surface, or a lens-shaped shape with a curved surface. A disk-shaped substrate to be polished is preferred. In the case of a disk-shaped substrate to be polished, its outer diameter is, for example, 10 to 120 mm, and its thickness is, for example, 0.5 to 2 mm.

[0054] In general, magnetic disks are manufactured by polishing a substrate that has undergone a grinding step through a rough polishing step and a finish polishing step, followed by a magnetic layer formation step. In one or more embodiments, the polishing composition of the present disclosure is preferably used for polishing in the rough polishing step. In one or more embodiments, the polishing composition of the present disclosure is a polishing composition for magnetic disk substrates.

[0055] [Method for reducing residual silica] In one aspect, the present disclosure relates to a method for reducing residual silica on a substrate after polishing, which comprises polishing a substrate to be polished with a polishing liquid composition of the present disclosure (hereinafter also referred to as the "method for reducing residual silica of the present disclosure"). Examples of the substrate to be polished in the method for reducing residual silica of the present disclosure include the above-mentioned substrate to be polished. In one or more embodiments, the method for reducing residual silica according to the present disclosure may further include selecting silica particles A (component A) to be contained in the polishing liquid composition according to the present disclosure. In the present disclosure, "selecting silica particles A" includes purchasing a product that describes in a catalog, product manual, label, or the like the physical properties of silica particles A (component A) and / or that the residual silica can be reduced. Therefore, in one or more embodiments, the method for reducing silica residue of the present disclosure relates to a method for reducing silica residue, which comprises selecting silica particles A (component A) and polishing a substrate to be polished using the polishing liquid composition of the present disclosure containing the selected silica particles A (component A). In another aspect, the present disclosure relates to a method for reducing residual silica, comprising selecting silica particles having an ignition loss of 4% or less on a dry weight basis as abrasive grains, and polishing a substrate to be polished using a polishing liquid composition containing the silica particles, a nitrogen-containing compound, and an aqueous medium, wherein the nitrogen-containing compound is an organic amine compound having four or less nitrogen atoms in its molecule. Examples of the silica particles used in the method for reducing residual silica of this aspect include the silica particles A (component A) described above. Examples of the nitrogen-containing compound used in the method for reducing residual silica of this aspect include the component D described above. Examples of the polishing liquid composition used in the method for reducing residual silica of this aspect include the polishing liquid composition of the present disclosure described above. According to the method for reducing residual silica of the present disclosure, by using the polishing composition of the present disclosure, in one or more embodiments, the removal rate can be improved without significantly increasing the amount of residual silica. Furthermore, in one or more other embodiments, the amount of residual silica on the substrate surface after polishing can be reduced while maintaining the removal rate. The specific polishing method and conditions can be the same as those of the substrate manufacturing method of the present disclosure, which will be described later.

[0056] [Polishing method] In one aspect, the present disclosure relates to a method for polishing a substrate (hereinafter also referred to as the "polishing method of the present disclosure"), which comprises polishing a substrate to be polished using the polishing liquid composition of the present disclosure, wherein the substrate to be polished is a substrate used in the manufacture of magnetic disk substrates. Examples of the substrate to be polished in the polishing method of the present disclosure include the substrates to be polished described above. The polishing method of the present disclosure can be used, for example, in a rough polishing step. According to the polishing method of the present disclosure, by using the polishing composition of the present disclosure, in one or more embodiments, the removal rate can be improved without significantly increasing the amount of residual silica. Furthermore, according to the polishing method of the present disclosure, in one or more other embodiments, the amount of residual silica on the substrate surface after polishing can be reduced while maintaining the removal rate. Therefore, the productivity of substrates (e.g., magnetic disk substrates) with improved substrate quality can be improved. Specific polishing methods and conditions can be the same as those of the substrate manufacturing method of the present disclosure, which will be described later.

[0057] [Method of manufacturing magnetic disk substrate] In one aspect, the present disclosure relates to a method for manufacturing a magnetic disk substrate (hereinafter also referred to as the "substrate manufacturing method of the present disclosure"), which includes a polishing step (hereinafter also referred to as the "polishing step") of polishing a substrate to be polished using the polishing liquid composition of the present disclosure. The polishing step in the substrate manufacturing method of the present disclosure is, for example, a rough polishing step. In one or more embodiments, the substrate manufacturing method of the present disclosure may further include a step of selecting silica particles A (component A) to be contained in the polishing liquid composition of the present disclosure. In the present disclosure, "selecting silica particles A" includes, as described above, purchasing a product that describes in a catalog, product manual, label, etc. the physical properties of silica particles A (component A) and / or that residual silica can be reduced. Therefore, in one or more embodiments, the substrate manufacturing method of the present disclosure relates to a method for manufacturing a magnetic disk substrate, which includes a step of selecting silica particles A (component A) and a step of polishing a substrate to be polished using the polishing liquid composition of the present disclosure containing the selected silica particles A (component A). In another aspect, the present disclosure relates to a method for producing a magnetic disk substrate, comprising the steps of selecting silica particles having an ignition loss of 4% or less on a dry weight basis as abrasive grains, and polishing a substrate to be polished using a polishing liquid composition containing the silica particles, a nitrogen-containing compound, and an aqueous medium, wherein the nitrogen-containing compound is an organic amine compound having four or less nitrogen atoms in its molecule. Examples of the silica particles used in the method for producing a magnetic disk substrate of this aspect include the silica particles (component A) described above. Examples of the nitrogen-containing compound used in the method for producing a magnetic disk substrate of this aspect include the component D described above. Examples of the polishing liquid composition used in the method for producing a magnetic disk substrate of this aspect include the polishing liquid composition of the present disclosure described above.

[0058] In the polishing step, for example, the substrate to be polished can be polished by sandwiching the substrate between platens to which polishing pads are attached, supplying the polishing liquid composition of the present disclosure to the polishing surface, and moving the polishing pad and the substrate to be polished while applying pressure.

[0059] From the viewpoint of ensuring the polishing rate and reducing short-wavelength waviness, the polishing load in the polishing step is preferably 3 kPa or more, more preferably 5 kPa or more, even more preferably 7 kPa or more, and preferably 30 kPa or less, more preferably 25 kPa or less, and even more preferably 20 kPa or less. More specifically, the polishing load is preferably 3 kPa or more and 30 kPa or less, more preferably 5 kPa or more and 25 kPa or less, and even more preferably 7 kPa or more and 20 kPa or less. In the present disclosure, "polishing load" refers to the pressure of the platen applied to the polished surface of the substrate during polishing. The polishing load can be adjusted by air pressure or weight load on the platen, substrate, etc.

[0060] In the polishing process, 2From the viewpoints of maintaining the polishing rate and reducing short wavelength waviness, the polishing amount per cm of the substrate to be polished is preferably 0.2 mg or more, more preferably 0.3 mg or more, and even more preferably 0.4 mg or more, and from the same viewpoint, it is preferably 2.5 mg or less, more preferably 2 mg or less, and even more preferably 1.6 mg or less. 2 The amount of polishing per unit area is preferably 0.2 mg or more and 2.5 mg or less, more preferably 0.3 mg or more and 2 mg or less, and even more preferably 0.4 mg or more and 1.6 mg or less.

[0061] The polished substrate in the polishing process 2 From the viewpoint of economic efficiency, the supply rate of the polishing composition per cm of the substrate to be polished is preferably 2.5 mL / min or less, more preferably 2 mL / min or less, and even more preferably 1.5 mL / min or less, and from the viewpoint of improving the polishing rate, it is preferably 0.01 mL / min or more, more preferably 0.03 mL / min or more, and even more preferably 0.05 mL / min or more. More specifically, 2 The supply rate of the polishing composition per unit time is preferably 0.01 mL / min to 2.5 mL / min, more preferably 0.03 mL / min to 2 mL / min, and even more preferably 0.05 mL / min to 1.5 mL / min.

[0062] The polishing composition of the present disclosure can be supplied to a polishing machine, for example, by continuous supply using a pump or the like. When supplying the polishing composition to a polishing machine, in addition to a method of supplying it as a single liquid containing all components, it can also be divided into a plurality of blending component liquids and supplied as two or more liquids, taking into consideration the storage stability of the polishing composition, etc. In the latter case, the plurality of blending component liquids are mixed, for example, in the supply pipe or on the substrate to be polished, to produce the polishing composition of the present disclosure.

[0063] According to the substrate manufacturing method of the present disclosure, by using the polishing liquid composition of the present disclosure, in one or more embodiments, the removal rate can be improved without significantly increasing the amount of residual silica. Furthermore, according to the substrate manufacturing method of the present disclosure, in another one or more embodiments, the amount of residual silica on the substrate surface after polishing can be reduced while maintaining the removal rate. Therefore, substrates (e.g., magnetic disk substrates) with improved substrate quality can be efficiently manufactured. [Example]

[0064] The present disclosure will be described in more detail below with reference to examples, but these are merely illustrative examples and the present disclosure is not limited to these examples.

[0065] 1. Preparation of Polishing Composition Silica particles (component A or non-component A), acid (component B), oxidizing agent (component C), nitrogen-containing compound (component D or non-component D), and water were mixed to prepare the polishing liquid compositions of Examples 1 to 5, Comparative Examples 1 and 2, and Reference Examples 1 to 4 shown in Table 1. The content (active content) of each component in the polishing liquid compositions of Examples 1 to 5 and Reference Examples 1 to 3 was as follows: silica particles (component A or non-component A): 5.5 mass %, acid (component B): 1.6 mass %, oxidizing agent (component C): 1.0 mass %, nitrogen-containing compound (component D or non-component D): 0.1 mass %. The content of water in the polishing liquid compositions of Examples 1 to 5 and Reference Examples 1 to 3 is the remainder excluding component A or non-component A, component B, component C, and component D or non-component D. The contents (active components) of each component in the polishing compositions of Comparative Examples 1 and 2 and Reference Example 4 were: silica particles (component A or non-component A): 5.5 mass %, acid (component B): 1.6 mass %, and oxidizing agent (component C): 1.0 mass %. The water content in the polishing compositions of Comparative Examples 1 and 2 and Reference Example 4 is the remainder excluding component A or non-component A, component B, and component C. The polishing compositions of Examples 1 to 5, Comparative Examples 1 and 2, and Reference Examples 1 to 4 did not contain alumina abrasive grains. The silica particles (component A) used as abrasive grains were produced by a water glass method. The pH of the polishing compositions of Examples 1 to 5, Comparative Examples 1 and 5, Comparative Examples 1 and 2, and Reference Examples 1 to 4 was 1.5. The pH was measured at 25°C using a pH meter (manufactured by DKK-TOA Corporation), and the value measured 2 minutes after immersing an electrode in the polishing composition was used.

[0066] The following components A, B, and C were used to prepare the polishing compositions. <Silica abrasive grains (component A or non-component A)> (Preparation of Silica Particles A1 to A2) To 500 g of a metal silicate solution adjusted to a pH of 10-12 and a silica concentration of 2%, 7 kg of an acidic silicic acid solution adjusted to a silica concentration of 5% is added intermittently over a period of 1 to 24 hours to increase particle size (build-up). By adjusting the addition rate, silicic acid concentration, reaction temperature, pressure, pH, and other factors, silica abrasive grains with a desired range of silanol groups can be obtained. In particular, slowing the addition rate to allow the particles to grow slowly results in the formation of a dense surface and internal structure, increasing the number of siloxane bonds, allowing the silanol groups and loss on ignition to be adjusted. By the above-mentioned production method, the following silica particles A1 to A5 were prepared. A1: Non-spherical silica particles [colloidal silica (water glass method), aspect ratio 1.09, average secondary particle diameter 160 nm] A2: Non-spherical silica particles [colloidal silica (water glass method), aspect ratio 1.12, average secondary particle diameter 142 nm] (Details of Silica Particles A3) A3: Non-spherical silica particles [precipitated silica, Nipsil E-743 manufactured by Tosoh Silica Corporation, crushed in a wet bead mill to adjust the average secondary particle size, aspect ratio 1.34, average secondary particle size 349 nm] <Nitrogen-containing compounds (component D or non-component D)> MEA: Monoethanolamine (molecular weight 61, nitrogen atom count 1) AEA: N-(β-aminoethyl)ethanolamine (molecular weight 104.5, number of nitrogen atoms 2) HEP: N-(2-hydroxyethyl)piperazine (molecular weight 130.19, number of nitrogen atoms 2): DETA: Diethylenetriamine (molecular weight 103.17, number of nitrogen atoms 3) TETA: Triethylenetetramine (molecular weight 146.23, number of nitrogen atoms 4) TEPA: Tetraethylenepentamine (molecular weight 189.3, number of nitrogen atoms 5) PEHA: Pentaethylenehexamine (molecular weight 232.37, number of nitrogen atoms 6) PEI: Polyethyleneimine (number average molecular weight 600, approximately 20 nitrogen atoms, "Epomin SP-006" manufactured by Nippon Shokubai Co., Ltd.) <Acid (component B)> Phosphoric acid [75% concentration, manufactured by Nippon Chemical Industry Co., Ltd.] <Oxidizing agent (ingredient C)> Hydrogen peroxide [35% by mass, manufactured by ADEKA]

[0067] 2.Measuring methods for each parameter [Method for measuring silica particle diameters D10, D50, and D90 by centrifugal sedimentation method (CPS measurement)] Silica particles were diluted with ion-exchanged water to prepare a dispersion containing 0.4 mass % of silica particles, which was used as a sample. The particle size distribution of the prepared sample was measured by centrifugal sedimentation using the following measuring device. The particle sizes at which the cumulative frequency from the small diameter side in the particle size distribution calculated by weight obtained by centrifugal sedimentation was 10%, 50%, and 90%, respectively, were defined as D10, D50, and D90. <Measurement conditions> Measurement device: CPS DC24000 UHR manufactured by CPS Instruments Measurement range: 0.02 to 3 μm Particle extinction coefficient: 0.1 Particle shape factor: 1.2 or 1.0 Rotation speed: 18,000 rpm Calibration standard particle size: 0.476μm Standard particle density: 1.0465 (13%, 34℃) Density gradient solution: sucrose aqueous solution (8%, 24%) Solvent viscosity: 1.16 cp (13%, 34°C) Refractive index of solvent: 1.3592 (18%, 34°C) Measurement temperature: 15~45℃ Measurement time: 3 to 420 minutes

[0068] [Method for measuring silica particle diameter D50 (average secondary particle diameter) using DLS measurement] Silica particles were mixed with phosphoric acid and ion-exchanged water to prepare a 1% by mass silica particle dispersion. The prepared 1% by mass silica particle dispersion was placed in the following measuring device and measured under the following conditions. In the obtained particle size distribution, the particle diameter at which the cumulative volume frequency from the small diameter side was 50% was taken as D50. Note that D50 measured by DLS was taken as the average secondary particle diameter (volume average particle diameter) of the silica particles. The measurement results are shown in Table 1. <Measurement conditions> Measurement equipment: Malvern Zetasizer Nano "Nano S" Sample volume: 1.5 mL Laser: He-Ne, 3.0mW, 633nm Scattered light detection angle: 173°

[0069] [Average aspect ratio of silica particles] Photographs of silica particles observed with a TEM (JEOL "JEM-2000FX", 80 kV, 10,000 to 50,000 magnification) were scanned into a personal computer as image data, and the projection images of 500 silica particles were analyzed using analysis software (Mitani Corporation "WinROOF (Ver. 3.6)") as described below. The minor axis and major axis of each silica particle were determined, and the average value of the aspect ratios (average aspect ratio) was calculated by dividing the major axis by the minor axis.

[0070] [Ignition loss] Silica particles were mixed with ion-exchanged water to prepare a 40 mass % silica slurry. The prepared silica slurry was adjusted to pH 3.5 with sulfuric acid and heated at 180°C using a Shimadzu MOC63u infrared moisture meter to remove moisture. It was then left to stand for 10 minutes and returned to room temperature, yielding 2g of sample. The loss on drying (LOD) (how much moisture it absorbs at room temperature) was measured again using the infrared moisture meter for 1g of the sample. The remaining 1g of sample was placed in a ceramic crucible and fired in a firing furnace at 1000°C for 2 hours, then allowed to cool in a desiccator for 30 minutes, after which the loss on ignition (LOI) (weight lost due to dehydration of silanol groups) was measured. Finally, the loss on ignition (WL) based on dry weight was calculated using the following formula: Loss on ignition (WL) on a dry weight basis = 100 × {1-(100-LOI) / (100-LOD)}

[0071] 3. Polishing the substrate Using the prepared polishing compositions of Examples 1 to 5, Comparative Examples 1 and 2, and Reference Examples 1 to 4, substrates to be polished were polished under the following polishing conditions.

[0072] [Polishing conditions] Polishing machine: Double-sided polishing machine (9B type double-sided polishing machine, manufactured by Speedfam) Substrate to be polished: Ni-P plated aluminum alloy substrate, thickness 0.8 mm, diameter 95 mm, number of substrates: 10 Polishing liquid: polishing liquid composition Polishing pad: Suede type (foam layer: polyurethane elastomer, thickness 1.0 mm, average pore size 30 μm, surface layer compressibility 2.5%, Filwel) Plate rotation speed: 40 rpm Polishing load: 9.8 kPa (set value) Polishing liquid supply amount: 100mL / min Substrate to be polished 1cm 2 Feed rate per unit: 0.8 mL / min Substrate to be polished 1cm 2 Polishing amount per piece: 0.8mg Polishing time: 5 minutes

[0073] 4. Evaluation Method [Evaluation of polishing speed] The removal rates of the polishing compositions of Examples 1 to 5, Comparative Examples 1 and 2, and Reference Examples 1 to 4 were evaluated as follows. First, the weight of each substrate was measured before and after polishing using a Sartorius "BP-210S" and the mass loss was calculated from the change in mass of each substrate. The average mass loss of all 10 substrates was divided by the polishing time to obtain the removal rate, which was then calculated using the following formula. The removal rate of Comparative Example 1 was then set to 100 and relative values ​​were calculated to be used as evaluation items. Mass loss (g) = {mass before polishing (g) - mass after polishing (g)} Polishing speed (g / min) = Mass reduction amount (g) / Polishing time (min)

[0074] [Silica Remaining Evaluation] The polished substrate was then cleaned using a cleaning machine manufactured by Hikari Corporation, and the intensity of the silica particles remaining on the substrate surface was measured using a fluorescent X-ray analyzer "ZSX100e" manufactured by Rigaku Corporation. Details are described below. The relative value was calculated, with the remaining silica in Comparative Example 1 taken as 100, and this was used as an evaluation item. <Cleaning conditions> Ultrapure water immersion time: 3 minutes Ultrasonic cleaning time: 3 minutes Brush cleaning time: 4 seconds Ultrapure water rinsing time: 10 seconds Spin dry time: 10 seconds <Fluorescent X-ray measurement conditions> After polishing and cleaning, the substrate was placed in the equipment without cutting, and the peak intensity of the Si element was detected to provide an index of the amount of remaining silica. A lower peak intensity of the Si element indicates less remaining silica. Measurement time: 300 seconds Opening degree: 30mm Detection angle: 2θ=47 degrees Peak detection angle: 144.610 Voltage: 50kv Current: 50mA Detection points: 8 arbitrary points per board As shown in the above measurements, by feeding the substrates into the equipment without cutting them, it is possible to reduce the risk of residual silica falling off due to the impact of cutting the substrate, the risk of foreign matter being mixed in, and the impact of variations per substrate.

[0075] 5.Results The results of each evaluation are shown in Table 1.

[0076] [Table 1]

[0077] As shown in Table 1, it was found that the polishing compositions of Examples 1 to 5, which used specified silica particles and a specific nitrogen-containing compound, were able to reduce silica residue while maintaining the polishing rate, compared to Comparative Examples 1 to 2 and Reference Examples 1 to 4. [Industrial Applicability]

[0078] According to the present disclosure, in one aspect, the removal rate can be improved without significantly increasing the amount of residual silica, and in another aspect, the removal rate can be maintained while reducing the amount of residual silica on the substrate surface after polishing, thereby improving the productivity of substrates with improved substrate quality. The present disclosure can be suitably used in the manufacture of magnetic disk substrates.

Claims

1. The composition contains silica particles, a nitrogen-containing compound, and an aqueous medium, The silica particles have an ignition loss of 4% or less on a dry weight basis; In the polishing composition, the nitrogen-containing compound is an organic amine compound having four or less nitrogen atoms in the molecule.

2. 2. The polishing composition according to claim 1, wherein the value represented by the following formula (I) is 150 or less, where WL is the loss on ignition and D90 is the particle size at which the cumulative frequency from the small particle size side in a particle size distribution converted into weight obtained by a centrifugal sedimentation method is 90%. {(WL) 3 ×D90} / 100 (I)

3. 2. The polishing liquid composition according to claim 1, wherein the silica particles have a particle diameter D10 of 50 nm or more and 120 nm or less, where D10 is the particle diameter at which a cumulative frequency from the small particle diameter side in a particle size distribution in weight conversion obtained by a centrifugal sedimentation method is 10%.

4. 2. The polishing liquid composition according to claim 1, wherein the silica particles have a particle diameter D50 of 80 nm or more and 340 nm or less, where D50 is the particle diameter at which a cumulative frequency from the small particle diameter side in a particle size distribution in weight conversion obtained by a centrifugal sedimentation method is 50%.

5. 2. The polishing composition according to claim 1, wherein the silica particles have a particle diameter D90 of 140 nm or more and 600 nm or less, where D90 is the particle diameter at which a cumulative frequency from the small particle diameter side in a particle size distribution calculated on a weight basis obtained by a centrifugal sedimentation method is 90%.

6. The polishing composition according to claim 1 , which is a polishing composition for a magnetic disk substrate.

7. A method for producing a magnetic disk substrate, comprising a polishing step of polishing a substrate to be polished with the polishing composition according to claim 1 .

8. 8. The method for producing a magnetic disk substrate according to claim 7, wherein the substrate to be polished is an aluminum alloy substrate plated with Ni--P.

9. The method for producing a magnetic disk substrate according to claim 7 , wherein the polishing step is a rough polishing step.

10. 6. A method for polishing a substrate, comprising polishing a substrate to be polished with the polishing composition according to claim 1, wherein the substrate to be polished is a substrate used in the manufacture of magnetic disk substrates.

11. 1. A method for reducing residual silica on a polished substrate, comprising: A method for reducing residual silica, comprising polishing a substrate to be polished with the polishing composition according to claim 1 .

12. selecting silica particles as the abrasive grains having an ignition loss of 4% or less on a dry weight basis; polishing a substrate to be polished using a polishing composition containing the silica particles, a nitrogen-containing compound, and an aqueous medium; The nitrogen-containing compound is an organic amine compound having four or less nitrogen atoms in the molecule.